Chávez’s Bolivarian Republic Viewed With a Quality Lens - Baker, Biff (Journal of Management Policy and Practice, 2021)
This research looks at Venezuela using project and quality parameters of excellence with discussion on the practical implementation, success, or failures from a project and quality management perspective. For context, the introduction covers key Venezuelan leaders who preceded Chávez; the literature review dives deeper into the Bolivarian 21st Century Socialist experiment with foci upon measurable outcomes of key policies. The paper concludes with a theoretical assessment model with recommendations for future research focused upon project and quality assessments, not mere politics. The quality model and associated research questions will assist government and multinational corporation researchers, as well as students of international business to conduct grounded, fact-based assessments.